MANAGEMENT SKILLS – TOOLS FOR LEADERSHIP IMPERATIVES IN DEMOCRACY - Abbass, Isah Mohammed (European Scientific Journal, ESJ, 2012)
In attaining the mission and vision of organizations, the employment of management skills are essential tools for leadership. The imperatives of such skills in dynamic organizations suggest effectiveness and efficiency. Democratic societies and organizations are expected to possess hybrid skills in the management of their affairs. It is no longer good for any organization to have the „right. leadership in the right place without the right management skills. In other words, it brings serious injuries to organizations when individuals are contracted without the corresponding expected performance. Performance, based on management skills, constitutes the vital hyphen for leadership in coordinating strategy and target in order to deliver services. Corporate governance therefore entails strategy, management and efficient output of products. All these require management techniques of planning, organising, leading, controlling etc. of all resources. This Paper attempts to generally x-ray management skills that provide essential tools for leadership in democracy. Since high performance organizations are identified with leaders that give them great virtues, they are thus characterized by „charismatic. and „transformational. leaders based on the vision and strategy employed. A few Nigerian situations were exhibited in order to show leadership qualities and styles as well as the essence of leadership imperatives in democracy. However, the feasibility of democracy in Nigeria and its desirability in organizational leadership have continued to raise crucial questions on management skills.